Physics of the Atmosphere and Climate / [electronic resource] - Salby, Murry L. (Cambridge : Cambridge University Press, 2012)
Murry Salby's new book provides an integrated treatment of the processes controlling the Earth-atmosphere system, developed from first principles through a balance of theory and applications. This book builds on Salby's previous book, Fundamentals of Atmospheric Physics. The scope has been expanded into climate, with the presentation streamlined for undergraduates in science, mathematics and engineering. Advanced material, suitable for graduate students and as a resource for researchers, has been retained but distinguished from the basic development. The book provides a conceptual yet quantitative understanding of the controlling influences, integrated through theory and major applications. It leads readers through a methodical development of the diverse physical processes that shape weather, global energetics and climate. End-of-chapter problems of varying difficulty develop student knowledge and its quantitative application, supported by answers and detailed solutions online for instructors.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Atmospheric physics